Pediatric Oncology Palliative Care Programs in Central America: Pathways to Success - Wendy Cristhyna Gómez García; Silvia Rivas; Gabriela Paz; Marisol Bustamante; Gerardo Castro; Hazel Gutiérrez; Maria Sabina Ah Chu; Pascale Yola Gassant; Rolando Larin Lovo; Yessika Gamboa; Marleni Torres Núñez; Ximena García Quintero; et al. (MDPI AG, 2021)
Palliative care offers children who have life-limiting and life-threatening oncologic illnesses and their families improved quality of life. In some instances, impeccable symptom control can lead to improved survival. Cultural and financial barriers to palliative care in oncology patients occur in all countries, and those located in Central America are no exception. In this article, we summarize how the programs participating in the Asociación de Hemato-Oncólogos Pediatras de Centro America (AHOPCA) have developed dedicated oncology palliative care programs. The experience in Guatemala, El Salvador, Costa Rica, Panama, Dominican Republic and Haiti is detailed, with a focus on history, the barriers that have impeded progress, and achievements. Future directions, which, of course, may be impacted by the COVID-19 pandemic, are described as well.